The right of private defence of a person: a comparative legal alignment - Mohamad Yunus, Mohamad Ismail (Serials Publications, 2015)
Islamic law as well as any other legal system, recognizes the individual or private rights in order to live in peace and harmony. If someone tries to violate one’s inherent right, Islamic law permits him, subject to certain conditions, to react in whatever manner he sees fit and proper without exaggeration in order to stop the aggression to his life, property, mind, religion, body and dignity. This reaction or “self-defence” is legally justifiable, supported by primary texts and jurists of all schools of law. According to the jurists in this situation the defender will not be held liable to either a civil or criminal charge. Therefore, the right of private defence is absolutely necessary for the protection of one’s person, habitation or property against the assailant who manifestly intends and endeavours to take them away. No doubt, it is the primary duty of the state to protect the life and property of its individual but no state, no matter how large its resources might be, can depute a policeman, to constantly watch the activities of each and every individual and protect him against the act of criminal. There may be some situations where help of the state authorities cannot be obtained in order to prevent an unlawful aggression either because no time is left to ask for such help or for any other reason. Therefore, in order to meet such exigencies, law has given the right of private defence to every individual. The main objective of this paper is to compare and contrast the nature, scope, application and development of the law relating to the right of self-defence under the Islamic and modern secular law, special focus to the Malaysian Penal Code in determining the consistency between the two legal system.